Socialization for Violence Prevention in Educational Institutions and Communities: A Psychoeducational and Legal Awareness Approach - Rahman, Maulida Aulia; ., Jamilah; Nurohman, Muhamad Rizky; Aulia, Nazma Rahma (Indonesian Journal of Community Empowerment (IJCE), 2025)
This article reports a multi-setting community outreach on violence prevention across higher education, Islamic boarding school and vocational school, secondary schools, and a village community in Garut, Indonesia. The program aimed to strengthen psychoeducational understanding and legal awareness regarding child protection and reporting pathways. Using a descriptive, participatory design, activities combined interactive lectures, case-based discussions, role-play, and storytelling; data consisted of observations, field notes, and participant testimonies. Findings indicate that participants could identify types of violence, demonstrated improved legal literacy and readiness to report, and practiced protective skills such as assertive refusal, help-seeking, and basic documentation. The outreach produced an adaptive, replicable socialization model suitable for diverse age groups and settings. The study concludes by recommending curricular integration, clear institutional SOPs, and visible referral maps to sustain safer learning environments.